Decarbonizing gas emissions from petrochemical production using microalgae - F. Shevlyakov; A.B. Laptev; O.R. Latypov; D.R. Latypova (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Greenhouse gas emissions are the primary cause of global warming. Under the Paris Agreement, all countries have developed programs to reduce anthropogenic impact on the environment. In the petrochemical industry, for example, isoprene, is a major contributor to the production of carbon dioxide, generating large amounts of acidic and hydrocarbon gases that are burned and released into the atmosphere. This study aimed to investigate the absorption of greenhouse gases from isoprene production by the marine microalgae Isochrysis galbana and Tetraselmis suecica, as well as the freshwater microalgae Chlorella vulgaris.METHODS: Microalgae cells were cultured in a bioreactor. The grown microalgae strains and mineralized water were fed to the bioreactor. Gases discharged from isoprene production were passed through the bioreactor. Inlet and outlet gas compositions were monitored by chromatography.FINDINGS: Absorption of gases discharged from isoprene production by microalgae was studied for the first time. Chlorella vulgaris microalgae reduced methane and carbon dioxide contents by an average of 20 times. A mixture of microalgae Tetraselmis suecica and Isochrysis galbana reduced methane and carbon dioxide contents by a factor of 10 but completely absorbed hydrocarbon gases from methane to pentane.CONCLUSIONS: The results indicate that microalgae cultivation can be used as a reliable and stable technology for the biofixation of the gases discharged in isoprene production. This technology can eliminate the combustion stage of hydrocarbon gases in isoprene production and significantly reduce carbon dioxide emissions into the atmosphere.